Lychnophoric acid from Lychnophora pinaster: a complete and unequivocal assignment by NMR spectroscopy - Silveira, Damaris; de Souza Filho, Jose Dias; de Oliveira, Alaide Braga; Raslan, Delio Soares (Eclética Química, 2005)
The investigation of the hexane extract from aerial parts of Lychnophora pinaster provided, besides others substances, the E-isomer of lychnophoric acid, a sesquiterpene derivative previously isolated from L. affinis.